Islamisme dan Politisasi Agama Model PKS dalam Pilpres 2009 - Muzakki, Akh. (Program Pascasarjana UIN Sunan Ampel Surabaya, 2010)
In the past decade or so, Islamism as a political concept and perhaps as an ideology has gained strong momentum in Indonesia. The fall of Soeharto after more than three decades in power has helped this ideology to emerge and exert itself particularly in the form of religion oriented political party. This paper is interested in exploring the expression and actualization of Islamism by scrutinizing the political behavior of Justice and Welfare Party (Partai Keadilan Sejahtera / PKS) during the 2009 presidential election. We are particularly interested in looking at the use of religious symbols and rites by the party for clear political purposes. We argue that Islamism has been manipulated by PKS during that election as a vehicle to gain power. Hence, the main problem that this paper deals with is actually the idea of the politization of religion by a political party claiming to have represented Islam and its noble teaching.